Features of Library Automation Software:A Comparative Study - Ravichandra Rao, I. K.; Sainul Abideen, P. (Journal of Information and Knowledge, 1999)
Discusses the need for automation in libraries. Gives an overview of the features and functions of library automation software. Also discusses the additional features which the library automation software should have in the context of Internet. Further, paper discusses the need for evaluation of the library automation software, factors to be considered, checklist used for selection and evaluation of library automation software. A comparative study of the features of selected packages is presented.